Complexity of ecosystem services in agricultural fields, in particular the biodiversity - Csíder, Ibolya (Acta Agraria Debreceniensis, 2015)
Since the Convention on Biological Diversity a lot of papers have been published how to measure and value biodiversity. In the last decades publications on agro-ecosystems become more frequent and play a significant role in the provision of ecosystem services. There is a uniform definition for biodiversity in general, however, in terms of agro-ecosystems and their services (including biodiversity) many weaknesses can be identified. The objective of this paper is to explore some of these problems with special regard to different definitions and terms and to the farmland ecosystem services. One solution could be to adopt a more complex system which has some ecological and environmental components (air, water and soil pollution) and also takes in to consideration the efficiency of agricultural production.